2000
DOI: 10.1093/brain/123.10.2020
|View full text |Cite
|
Sign up to set email alerts
|

Expression of accessory molecules for T-cell activation in peripheral nerve of patients with CIDP and vasculitic neuropathy

Abstract: Vasculitic neuropathy and chronic inflammatory demyelinating polyneuropathy (CIDP) are neuropathies characterized by a T-lymphocyte infiltrate in the peripheral nerves. The microenvironment in which these T cells become activated, and the molecules and cells that play a role in this process are incompletely understood. Using immunohistochemical analysis, we studied the effect of the presence of adhesion, costimulatory and antigen-presenting molecules on different cell types as a precondition for local T-cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 43 publications
1
52
1
Order By: Relevance
“…The expression of costimulatory proteins on Schwann cells is currently controversial. Whereas one group reported the presence of CD80 molecules on cultured primary Schwann cells (13), another study failed to detect CD80 and CD86 proteins in normal nerve tissue (9). Under the culture conditions used in the current study, we were unable to detect expression of CD80 on primary Schwann cells (data not shown).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The expression of costimulatory proteins on Schwann cells is currently controversial. Whereas one group reported the presence of CD80 molecules on cultured primary Schwann cells (13), another study failed to detect CD80 and CD86 proteins in normal nerve tissue (9). Under the culture conditions used in the current study, we were unable to detect expression of CD80 on primary Schwann cells (data not shown).…”
Section: Discussioncontrasting
confidence: 71%
“…In general, expression of CD1d proteins on Schwann cells was weak, and its clear demonstration required the use of staining procedures involving several steps of amplification. This observation may explain the failure to detect CD1d on nerve sections in a previous study (9). Nonetheless, the level of CD1d expression on Schwann cells was comparable to that expressed on monocyte-derived DCs, which are known to be potent iNKT activators in cell culture assays.…”
Section: Discussionmentioning
confidence: 81%
“…Given the dearth of data on NSVN, the group reviewed studies that enrolled patients with SVN or NSVN. Eighteen articles were selected, six class II and twelve class III (all case-control studies, except one retrospective cohort survey) 14,34,54,60,[94][95][96][97][98][99][100][101][102][103][104][105][106][107] , which were analysed to identify variables associated with vasculitic neuropathy. By combining evidence from this review with that from class IV studies that showed active axonal degeneration to be increased in all vasculitic neuropathy series, the guideline group designed consensus diagnostic criteria for histopathologically probable vasculitic neuropathy.…”
Section: Histopathological Diagnosismentioning
confidence: 99%
“…As demyelination and cell death ensue, immune complexes and complement products may be deposited in VN nerves (51,105), leading to more efficient clearing of the debris by activated macrophages. Whether there is an increase in T lymphocytes relative to normal controls is controversial (24,321). If present, T cells may have been attracted to the region primarily as the result of the underlying vasculitis and appear to be infiltrating into the nerve due to ischemic-induced blood-nerve barrier breakdown.…”
Section: C) Evidence For Ischemia-induced Nerve and Immune Changesmentioning
confidence: 99%